PENINGKATAN KAPASITAS TENAGA PENDAMPING DALAM PROGRAM EKONOMI KREATIF PADA YAYASAN BINA SURYA MANDIRI - Dewi Lola Millenia; Fortuna Sayyidinaa; Nadya Aulia Dwi Utami; Tasya Ameliani (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2020)
Human Resources are something that humans are born with. Human resource development itself aims to train the quality of these individuals. One example of training the quality of individuals is the Human Resource Development activity in the handicraft field at the Bina Surya Mandiri Foundation. This study aims: 1) to identify the process of human resources assistances at the Bina Surya Mandiri Foundation, 2) to increase the creativity of the children at the Bina Surya Mandiri Foundation. Apart from increasing the creativity of the children at the Bina Surya Mandiri Foundation, this activity also aims to develop the quality and quantity of Human Resources at the Bina Surya Mandiri Foundation, especially in the field of crafts. This research itself uses a descriptive-qualitative approach which was includes interviews, observation and documentation. This study showed that children at Bina Surya Mandiri Foundation have participated in handicraft activities well, and they hold handicraft activities of course with easy materials so that children at the Foundation can easily participate in these handicraft activities.